PENGARUH BUDAYA ORGANISASI, KOMUNIKASI ORGANISASI DAN KONFLIK TUGAS TERHADAPKINERJA KARYAWAN PADA PT. ASTRA HONDA MOTOR DI DENPASAR - Suwandana, I Made Adi; Susandya, Anak Agung Arie (JUIMA : JURNAL ILMU MANAJEMEN, 2018)
This research raised the title of the influence of organizational culture, organizational communication and task conflict on employee performance at PT. Astra Honda Motor in Denpasar. The formulation of the problem from this research is whether organizational culture, organizational communication and task conflict have significant effect simultaneously and individually to employees performance at PT. Astra Honda Motor in Denpasar and Among the variables of organizational culture, organizational communication and conflict of which task dominant influence on employee performance at PT. Astra Honda Motor in Denpasar. The purpose of this study is to test the significance of the effect simultaneously and individually between organizational culture, organizational communication and task conflict on employee performance at PT. Astra Honda Motor in Denpasar and to find out which variables between organizational culture, organizational communication and task conflict that have dominant influence on employee performance at PT. Astra Honda Motor in Denpasar. Population in this research is employees of PT. Astra Honda Motor in Denpasar 2015 as many as 92 people. The results showed that from the results of F statistical tests (F-test) obtained obtained F-count is 35.301 larger than F-table of 2.71 with sig. 0.000 <0.05 is in the rejection area of ​​Ho, then Ho is rejected or H1 accepted, it is true there is a positive and significant relationship (significant) simultaneously between organizational culture, organizational communication and task conflict with employee performance on PT. Astra Honda Motor in Denpasar. The result of statistical test t (t-test) obtained t1-count is 3.905 with sig. 0.000 <0,05 bigger than t-table equal to 1,987 is in rejection region Ho, hence Ho refused or H2 accepted, it is true organizational culture have positive and significant effect to employee performance. The result of statistical test t (t-test) obtained t2-arithmetic is 5,552 with sig. 0.000 <0,05 bigger than t-table equal to 1,987 is in rejection area Ho, hence Ho refused or H2 accepted, it is true communications organization have positive and significant effect to employee performance. The result of statistical test t (t-test) obtained t3-count is 2,442 with sig. 0,017 <0,05 bigger than t-table equal to 1,987 is in rejection area Ho, hence Ho refused or H2 accepted, it is true conflict of duty have positive and significant effect to employee performance.